Building Eco-Friendly Cities: Government-Community Collaboration in Shaping Sustainable Urban Waste Management - Tuanaya, Wahab (Universitas Pattimura, 2024)
This article explores the collaborative role of government and community in shaping sustainable urban waste management as a foundation for building eco-friendly cities. Focusing on Ambon City, this research aims to understand how synergistic partnerships between local authorities and residents contribute to effective and sustainable waste governance. Utilizing a qualitative approach, data were collected through in-depth interviews with officials from the city’s Environmental and Waste Management Agency, supported by field observations and document analysis. The findings reveal that community participation and government support are both essential for addressing urban waste challenges, particularly in contexts where public awareness remains limited. The study identifies that collaboration enables the co-creation of contextually relevant policies, increases public compliance, and improves the effectiveness of waste management practices. The novelty of this study lies in its proposition of sustained, dialogic collaboration as a strategic model for urban waste governance, moving beyond top-down interventions toward more participatory and adaptive approaches. This research contributes to the development of social sciences and humanities by offering an integrated framework that connects environmental sustainability, civic engagement, and public policy. It recommends capacity-building initiatives, community-based programs, and policy reforms to strengthen the alignment between governmental infrastructure and community-led action for sustainable urban futures.